If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(2x + -4) + -1 = -1 Reorder the terms: 3x(-4 + 2x) + -1 = -1 (-4 * 3x + 2x * 3x) + -1 = -1 (-12x + 6x2) + -1 = -1 Reorder the terms: -1 + -12x + 6x2 = -1 Add '1' to each side of the equation. -1 + -12x + 1 + 6x2 = -1 + 1 Reorder the terms: -1 + 1 + -12x + 6x2 = -1 + 1 Combine like terms: -1 + 1 = 0 0 + -12x + 6x2 = -1 + 1 -12x + 6x2 = -1 + 1 Combine like terms: -1 + 1 = 0 -12x + 6x2 = 0 Solving -12x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6x'. 6x(-2 + x) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Solution
x = {0, 2}
| x+y=325 | | -9.6+x=-13.5 | | 22-7m= | | 5(x-2)=5-2x | | x-5.5=8.6 | | 21a^5+211a^3b^2+10ab^4=0 | | 5(4x+2)=3(6x+3) | | 17*n=51 | | 4(2x-3)=2(5x+2) | | 36-n=15 | | 5x-2x-7x-3x=18+6-24-6 | | 4(4x+5)=6(6x-3) | | 12=g/4-3 | | y(70-20y+10)=0 | | y(70-2y+10)=0 | | (2+y)(3y-8)=0 | | y(70-2+y+10)=0 | | a*6+7=11 | | 39xn=3 | | x(70-10)=0 | | 3(5-3x)=25 | | 39/:n=3 | | 70-20+y+10=0 | | 18+-1n=10 | | -3(-3)+2(-3)-3=0 | | 34xn=34 | | 3[d+12]=8-4d | | 9(-9)-10(-9)+9=0 | | (9)9-10(9)+9=0 | | -5x+3=6x-2 | | 9+9=(5+4m) | | 39/n=3 |